Employee Engagement, Work-Life Balance, and Innovative Performance among Public and Private Employees in Central Jakarta - Mamik Setiyorini; Eeng Ahman; Ade Sobandi; Rofi Rofaida (Journal of Economics and Management, 2026)
Indonesia's ranking in the Global Innovation Index declined from 54th in 2024 to 55th in 2025, highlighting the need to examine innovative performance at the individual level. This study analyzes the effect of employee engagement on innovative performance and evaluates work-life balance as a moderating variable among Generation Y and Generation Z employees in government and private sectors in Central Jakarta. A quantitative explanatory survey approach was used. The questionnaire consisted of 27 measurement items; the minimum sample requirement was 135 respondents, and 139 completed responses were analyzed using SmartPLS 4. The validity test produced AVE values of 0.666 for employee engagement, 0.685 for innovative performance, and 0.731 for work-life balance. Cronbach's Alpha values were 0.936, 0.942, and 0.953, respectively. Hypothesis testing showed that employee engagement significantly affected innovative performance (O = 0.831; T = 9.860; P = 0.000), while work-life balance significantly moderated that influence with a negative interaction coefficient (O = -0.133; T = 3.173; P = 0.002). The negative coefficient indicates that work-life balance attenuates, rather than strengthens, the engagement-innovative performance relationship. The findings suggest that organizations should enhance engagement while designing work-life balance practices that help younger-generation employees allocate energy sustainably for innovation.